Do Commercial Place Managers Explain Crime Across Places? Yes and NO(PE) - Tucker, Riley (Journal of quantitative criminology, 2024)
ObjectivesSome criminologists of place have argued that property owners and place managers are the key actors exerting guardianship over crime and driving differences in crime across places, giving rise to the “Neighborhoods Out of Places Explanation” (NOPE) theory of crime. However, research to date has yet to fully evaluate if crime statistically varies across properties, their owners, or surrounding geographies.MethodsData scraped from Yelp.com is used to identify 1070 land parcels that had at least one business receiving reviews from 2014 to 2020. 911 dispatches for disturbances are linked to parcels and measured as the rate of events per Yelp reviewer in the average year. Hierarchical negative binomial modeling-based variance decomposition techniques are used to evaluate how variation in disturbance rates is distributed across parcels, owners, census blocks, and census tracts. Hierarchical negative binomial models are used to assess the correlates of disturbance rates. Sensitivity analyses assess the correlates of disturbance rates using a single-level negative binomial model with bootstrapped standard errors as well as an alternative outcome measure based on count of 911 events.ResultsCommercial disturbance rates vary across parcels, parcel owners, and blocks. At the parcel level, higher Yelp ratings are associated with lower disturbance rates while parcel square footage and land value are associated with increased disturbance rates. Additionally, parcel-level crime disturbance rates are explained by block features such as poverty, violent crime, and the number of Yelp restaurants on the block.ConclusionsParcel, owner, and block features can all help explain why some restaurants have more crime than others. Future research should build on the place management perspective by investigating the wider breadth of potential actors who may exert guardianship over properties while acknowledging that offenders and targets systematically vary across geographies, making effective guardianship more difficult in some locations than others.